Determination of Hydronephrosis Causes In Pediatric Patients Using CT - O'hood Al-Hussein Mohammed; Ikhlas Abdelaziz Hassan; Mohamed Ahmed Ali; Hussein Ahmed Hassan (Asian Journal of Medical Radiological Research, 2012)
The objectives of this study were to evaluate the accuracy of computerized tomography urography (CTU) in diagnosinghydronephrosis in pediatric Patient (less than 15 years), minimize the radiation dose , examination cost , and time to reach the finaldiagnoses. This study carried out in two hospitals: Fedail hospital and Ibn-Alhaytham Diagnostic Center, during the period fromJuly 2012 to January 2013. Siemens somatom sensation 16 slice helical CT scan apparatus was used. Abdomen routine protocolwas performed with or without administration contrast medium. A total of 63 patients their ages are (1-14 years) withhydronephrosis . CTU detected the underlying pathology of hydronephrosis in 59 patients (93.7%). CT has become superiormodality for diagnosing the underlying pathology of hydronephrosis , and concluded to that CTU is the best protocol fordemonstration the underlying pathology of hydronephrosis than other modalities as ultrasound (U/S) and intravenous urography(IVU).The objectives of this study are to evaluate the ability of CT in the diagnosing of the urinary system diseases of pediatric inorder to assesses CT in cases of hydronephrosis in pediatric Patient (less than 15 years).